2008
DOI: 10.1590/s0103-21002008000500007
|View full text |Cite
|
Sign up to set email alerts
|

Evolução clínica de pacientes com insuficiência renal aguda em unidade de terapia intensiva

Abstract: Objective: To evaluate the clinical outcome of acute renal failure (ARF) patients when submitted to dialysis and non-dialysis treatments in ICU. Methods: this prospective study included patients over 18 years of age and serum creatinine of >1.5 mg/dl. The patients were included in dialysis and non-dialysis groups. Results: The study included 70 patients, 19 (27.1%) comprised the dialysis group and 51 (72.9%) the non-dialysis group. In the dialysis group, mortality rate was 42.1% and in the non-dialysis group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
2
6
0
12
Order By: Relevance
“…15 In this study, most of the infected patients were male and were hospitalized in the ICU, characteristics that are similar to the results of other studies. [16][17] The superiority of the hemodialysis temporary catheter insertion due to ARF was about five-fold higher compared with CRF, which was also observed in other studies. [18][19] This is possibly caused by the delay in the referral of these patients to the nephrologist, with a need for emergency hemodialysis and cases of ARF that is secondary to other diseases.…”
supporting
confidence: 72%
“…15 In this study, most of the infected patients were male and were hospitalized in the ICU, characteristics that are similar to the results of other studies. [16][17] The superiority of the hemodialysis temporary catheter insertion due to ARF was about five-fold higher compared with CRF, which was also observed in other studies. [18][19] This is possibly caused by the delay in the referral of these patients to the nephrologist, with a need for emergency hemodialysis and cases of ARF that is secondary to other diseases.…”
supporting
confidence: 72%
“…No estudo, foi encontrada a incidência de 44,7% de desenvolvimento de IRA em pacientes internados em UTI, sendo que na literatura científica existem estudos com incidência inferior, tais como 29% (9) , 29,7% (10) , 31,2% (2) e 35,7% (11) . E um estudo com incidência superior com 76,5% (12) .…”
Section: Discussionunclassified
“…Yet, the 2007 National Census showed that 73,605 patients were in dialytic treatment, of which 90.8% were undergoing hemodialytic treatment (7) . During the dialytic treatment, patient comorbidity is high and associated with cardiovascular diseases, systemic arterial hypertension, anemia, susceptibility to infection, high prevalence of types B and C hepatitis, bone diseases, malnutrition and other less-defined causes (8) .…”
Section: Introductionmentioning
confidence: 99%